Remarkable body architecture of marine sponges as biomimetic structure for application in tissue engineering - Martins, Eva (2019)
Recent advances in the study of marine environment, particularly of marine organismsâ architecture and composition, have isolated interesting compounds as proteins, GAG-like polysaccharides and bioactive compounds. These compounds have allowed the development of panoply of biomaterials inspired by morphological characteristics and anatomical structures of the marine species. Besides, the scientific community acknowledges the enormous biotechnological potential in the marine resources that can be a promising effective and efficient alternative to be used in Human health, namely tissue engineering and regenerative medicine, as well as to support the progress in pharmacological, cosmetic, nutraceutical and biomedical fields. Additionally, sustainable ways are being applied to explore these marine resources and address biomimetic approaches, aiming to take the most out of the astonishing marine environment in ecologically compatible ways. Marine sponges are a particular group of organisms feeding these biotechnological developments for human health, both as source of new drugs or inspiration for the development of marine biomaterials. This chapter aims to demonstrate, in a concise and clear way, the biotechnological potential of marine sponges used as susceptive bioscaffolds for regenerative medicine and biomedical applications in general.